The Implementation of Interactive Learning Technology to Enhance Elementary School Students Interest and Academic Achievement - La Ode Muheiman (Mauve Journal De Leardu, 2024)
This literature review aims to examine the impact of interactive learning technology on elementary school students' interest and academic achievement. The rapid advancement of educational technology has provided various tools, such as digital games, simulations, and interactive learning platforms, which have been shown to foster greater engagement and improve learning outcomes. This study synthesizes findings from recent research published between 2019 and 2024. The results indicate that interactive learning technologies significantly enhance student motivation, engagement, and cognitive performance when properly integrated into the learning environment. However, challenges remain, such as limited infrastructure, unequal access, and insufficient teacher training, particularly in developing countries like Indonesia. This review highlights the need for further empirical studies and policy interventions to support the effective implementation of technology in primary education.